15 let Osrednje družboslovne knjižnice Jožeta Goričarja - Jug, Janez (Družboslovne razprave, 1999)
This article presents the history of the Central Social Sciences Library Jože Goričar, its precedent libraries, as well as the automation process of library functions. The library had been founded in 1985 by the merging of theLibrary of the Sociological Institute and the Library of the Faculty of Sociology, Political Sciences and Journalism. The automation process began in 1978 when the Social Science Information Centre was founded, which covered the computer processing of bibliographic data. In 1993 the library entered the system of cooperative cataloguing COBISS and in 1994 included the bibliography of the Faculty of Social Sciences into the system. The automation was completed by 1995 with the automation of the lending segment of library functions.
Keywords: knjižnice; specialne knjižnice; Osrednja družboslovna knjižnica Jožeta Goričarja; 15 let